Soluble Non-ammonia Nitrogen in Ruminal and Omasal Digesta of Korean Native Steers Supplemented with Soluble Proteins - Choi, C W (Asian-Australasian journal of animal sciences, 2012)
An experiment was conducted to study the effect of soluble protein supplements on concentration of soluble non-ammonia nitrogen (SNAN) in the liquid phase of ruminal (RD) and omasal digesta (OD) of Korean native steers, and to investigate diurnal pattern in SNAN concentration in RD and OD. Three ruminally cannulated Korean native steers in a 3×3 Latin square design consumed a basal diet of rice straw and corn-based concentrate (control), and that supplemented (kg/d DM basis) with intact casein (0.24; IC) or acid hydrolyzed casein (0.46; AHC). Ruminal digesta was sampled using a vacuum pump, whereas OD was collected using an omasal sampling system at 2.0 h intervals after a morning feeding. The SNAN fractions (free amino acid (AA), peptide and soluble protein) in RD and OD were assessed using the ninhydrin assay. Concentrations of free AA and total SNAN in RD were significantly (p<0.05) lower than those in OD. Although free AA concentration was relatively high, mean peptide was quantitatively the most important fraction of total SNAN in both RD and OD, indicating that degradation of peptide to AA rather than hydrolysis of soluble protein to peptide or deamination may be the most limiting step in rumen proteolysis of Korean native steers. Diurnal variation in peptide concentration in OD for the soluble protein supplemented diets during the feeding cycle peaked 2 h post-feeding and decreased thereafter whereas that for the control was relatively constant during the entire feeding cycle. Diurnal variation in peptide concentration was rather similar between RD and OD